Effect of Topically Administered Chitosan-N-acetylcysteine on Corneal Wound Healing in a Rabbit Model. (12th June 2017) - Fischak, Corinna; Klaus, Robert; Werkmeister, René M.; Hohenadl, Christine; Prinz, Martin; Schmetterer, Leopold; Garhöfer, Gerhard
Abstract : Purpose . The present study was performed to investigate the effect of topically administered chitosan- N -acetylcysteine (C-NAC) on corneal wound healing in a rabbit model. Methods . A total of 20 New Zealand White rabbits were included in the randomized, masked, placebo-controlled experiment. A monocular epithelial debridement was induced by manual scraping under general anesthesia. Animals were randomized to receive either C-NAC two times daily or placebo. Monitoring of corneal wound healing was performed with ultra-high-resolution optical coherence tomography (OCT) and epithelial fluorescein staining. Measurements were done immediately after and up to 72 hours after wound induction. Results . No difference in wound size was found immediately after surgical debridement between the C-NAC group and the placebo group. Wound healing was significantly faster in the C-NAC group compared to the placebo group (p < 0.01 for both methods). A good correlation was found between the OCT technique and the epithelial fluorescein staining in terms of wound size (r = 0.94 ). Conclusions . Administration of C-NAC containing eye drops twice daily leads to a faster corneal wound healing in a rabbit model of corneal debridement as compared to placebo. Ultra-high-resolution OCT is considered a noninvasive, dye-free alternative to conventional fluorescein staining in assessing corneal wound healing also in humans.